Pre-martensitic phenomena in Ti40.7Hf9.5Ni44.8Cu5 shape memory alloy. (December 2015) - Resnina, N.; Belyaev, S.; Shelyakov, A.; Rubanik, V.; Rubanik, V.; Konopleva, R.; Chekanov, V.; Ubyivovk, E.; Krzhizhanovskaya, M.
Abstract: Pre-martensitic phenomena such as abnormal resistivity growth, diffusion scattering, "tweed" contrast and internal friction peak were observed in Ti40.7 Hf9.5 Ni44.8 Cu5 alloy prior to the forward martensitic transformation on cooling. It was shown that all the observed phenomena were due to the formation of quasi-static strain nanodomains in the B2 phase prior to the forward martensitic transformation. This led to accumulation of the elastic energy before the phase transition and resulted in the variation in thermodynamic balance for the forward martensitic transformation and, as a result, influenced the parameters of the phase transition. The appearance of elastic energy prior to the forward transformation caused a decrease in the forward and reverse martensitic transformations' start temperatures, a widening of the temperature range of the reverse transformation and an increase in the hysteresis of the transformation. Highlights: Pre-martensitic phenomena are observed in studied alloy before phase transition. Pre-martensitic phenomena are due to the formation of strain nanodomains. Formation of strain nanodomains on cooling leads to accumulation of elastic energy. Af – Ms value does not characterize the transformation hysteresis in studied alloy. Unusual parameters of MT are caused by the formation of strain nanodomains.